Effect of phosphorus and sulphur on yield and quality of soybean (Glycine max) in Typic Haplustept - Meena, Inderraj; Meena1, R.H.; Sharma, S.K.; Jat, Gajanand; Choudhary, J.L. (Annals of Agricultural Research, 2016)
A field experiment was conducted at the Instructional Farm of Rajasthan College of Agriculture, Udaipur (Rajasthan) during kharif season of 2012 using randomized block design with three replications to study the effect of phosphorus and sulphur on yield and quality of soybean in Typic Haplustept soils. The experiment consisted of four levels of phosphorus (0, 20, 40 and 60 kg P2O5/ ha) and four levels of sulphur (0, 15, 30 and 45 kg S/ha) applied through DAP and gypsum, respectively. The results revealed that each successive increasing levels of phosphorus and sulphur treatments individually and in combination significantly increased the plant height, pods per plant, seeds per pod, test weight, grain yield, stover yield, biological yield, protein content, oil content and oil yield as compared to control. The combined application of phosphorus and sulphur fertilizers was found to increase grain and stover yield as compared to their individual application. The highest grain yield (2141 kg/ha) and stover yield (3847 kg/ha) was obtained under 60 kg P2O5/ha and 30 kg S/ha (P60S30) treatment.